Splenogonadal Fusion – Not Just Another Hydrocoele - Kennedy, KP (The Royal College of Surgeons of England, 2006)
Splenogonadal fusion is a rare congenital abnormality. In this case report, the diagnosis of splenogonadal fusion was made after the removal of an abnormal mass at ‘routine’ left herniotomy. A cautious approach at surgery resulted in no apparent damage to the testicle. A short review of the literature is included.